PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PENDEKATAN KONSTRUKTIVISME PADA MATERI SISTEM SIRKULASI KELAS XI SMA - Wan Syafi'i; Arnentis "; Kartika " (Biogenesis, 2016)
ABSTRACT The aim of this study is develop of student worksheets based on constructivism on sirculation system for biology subject of class XI Senior High School. This development consisted of six student worksheets. This study was conducted in Biology Education Program University of Riau and Senior High School Babussalam Pekanbaru on September to December 2015. Validation sheets and student responses sheets were used as data collection instruments. Validation sheets were filled by the internal and external vaidators. Student responses sheet were filled by student class XI Senior High Scholl Babussalam Pekanbaru. The development of student worksheets use 4D pendekatan that consists of define, design, develop and disseminate but only until develop. Collected datas were analyzed by descriptive statistics. The result of this worksheets development showed that the student worksheets were very valid with score 3.38-3.64. Student responses to the worksheet were very good with score 3.33-3.72. Based on validation result and student responses, this students worksheets based on contruktivism approach could be implemented with filed test. Key words: Constructivism, Development, Student Worksheet, Sirculation System